2001
DOI: 10.1590/s0034-89102001000300002
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model for malaria transmission relating global warming and local socioeconomic conditions

Abstract: ObjectiveSensitivity analysis was applied to a mathematical model describing malaria transmission relating global warming and local socioeconomic conditions. Methods A previous compartment model was proposed to describe the overall transmission of malaria. This model was built up on several parameters and the prevalence of malaria in a community was characterized by the values assigned to them. To assess the control efforts, the model parameters can vary on broad intervals. ResultsBy performing the sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 9 publications
(26 reference statements)
0
18
0
3
Order By: Relevance
“…En este modelo se considera que tanto las personas como la enfermedad pueden migrar a diferencia de lo expuesto en [43] donde se propone que solamente existe migración de personas. Un análisis de la trasmisión de la malaria a partir de un modelo matemático de compartimientos que tiene en cuenta el calentamiento global y las condiciones socioeconómicas se puede apreciar en [49]. Se proponen siete compartimientos para los humanos con sus respectivas ecuaciones diferenciales: susceptibles, infectados pero no infecciosos, infecciosos, inmune, parcialmente inmune, no inmune pero con memoria inmunológica y en incubación después de una reinfección.…”
Section: Propagación De Enfermedadesunclassified
“…En este modelo se considera que tanto las personas como la enfermedad pueden migrar a diferencia de lo expuesto en [43] donde se propone que solamente existe migración de personas. Un análisis de la trasmisión de la malaria a partir de un modelo matemático de compartimientos que tiene en cuenta el calentamiento global y las condiciones socioeconómicas se puede apreciar en [49]. Se proponen siete compartimientos para los humanos con sus respectivas ecuaciones diferenciales: susceptibles, infectados pero no infecciosos, infecciosos, inmune, parcialmente inmune, no inmune pero con memoria inmunológica y en incubación después de una reinfección.…”
Section: Propagación De Enfermedadesunclassified
“…Rafikov et al [5] reported an efficient control strategy of malaria vector with the aid of genetically altered mosquitoes. Yang [6] suggested another approach for describing the malaria transmission connected with global warming and local socioeconomic circumstances. In a recent work, Senthamarai et al [7] utilized the HAM to examine the spreading of malaria illness in an SIRS-SI model.…”
Section: Introductionmentioning
confidence: 99%
“…The disease, schistosomiasis, also known as bilharziasis or snail fever, is a parasitic disease that was first named bilharzia [8,9] and it is prevalent in several regions of the 2 Epidemiology Research International developing world, predominantly Africa, South America, and Asia, with about 650 million people living in the endemic areas [10]. It is known that estimated 207 million people are infected, where 85 percent lives in underdeveloped areas of Africa [11], resulting in about 15,000 deaths annually presently [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that estimated 207 million people are infected, where 85 percent lives in underdeveloped areas of Africa [11], resulting in about 15,000 deaths annually presently [2]. Children below the age of 14 are the major victims of schistosomiasis infection in many parts of the world [10]. The basis of illness in victims is the eggs laid by the parasitic flat worms, that is, blood flukes of the genus Schistosoma [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation